Seed removal by the squirrel Notocitellus adocetus (Rodentia: Sciuridae) in Western México - Flores-Alta, Daniel (2023)
Introduction: Seed dispersal and seed predation have important impacts on plant diversity and community structure. Rodents participate in both of these types of interactions. Objectives: The objective of this study was to evaluate the removal of the seeds of Crescentia alata, Randia capitata, and Zea mays by the squirrel Notocitellus adocetus to determine how it affects these plant species, dispersing or preying on their seeds. Methods: We observed foraging and used camera traps to determine the part of the fruit (seed and/or pulp) consumed by the squirrels and the amount of fruit or seed consumed. We also placed fine sand traps (FST) to measure the percentage of seed removal. We quantified the fruits produced by the plant species studied and the percentage of damage caused by N. adocetus throughout the plots. Results: Notocitellus adocetus feeds on the seeds and pulp of C. alata and Z. mays. The species with the highest removal rate and the highest percentage of damage was C. alata. Zea mays was the plant species that had the highest percentage of removal from FST, the largest number of fruits, and the lowest percentage of damage. On FST, R. capitata had the lowest seed remotion. Conclusions: Notocitellus adocetus is considered a seed predator; however, due to its behavior and the characteristics of the fruits of C. alata and R. capitata, this rodent could make the seeds available to secondary seed dispersers.